2019
DOI: 10.3747/co.26.4481
|View full text |Cite
|
Sign up to set email alerts
|

Initial Management of Small-Cell Lung Cancer (limited- and Extensive-Stage) and the Role of Thoracic Radiotherapy and First-Line Chemotherapy: A Systematic Review

Abstract: Background Patients with limited-stage (ls) or extensive-stage (es) small-cell lung cancer (sclc) are commonly given platinum-based chemotherapy as first-line treatment. Standard chemotherapy for patients with ls sclc includes a platinum agent such as cisplatin combined with the non-platinum agent etoposide. The objective of the present systematic review was to investigate the efficacy of adding radiotherapy to chemotherapy in patients with es sclc and to determine the appropriate timing, dose, and schedule of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 64 publications
1
14
1
Order By: Relevance
“…The importance of surgery in the treatment early-stage SCLC has been widely acknowledged (19, 21, 22). And for SCLC patients at relatively advanced limited-stage, concurrent chemo-radiotherapy is greatly recommended (23, 24). Recent advances in radiology have enabled the early diagnosis of SCLC, and have prompted us to re-evaluate the effectiveness of surgery in SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of surgery in the treatment early-stage SCLC has been widely acknowledged (19, 21, 22). And for SCLC patients at relatively advanced limited-stage, concurrent chemo-radiotherapy is greatly recommended (23, 24). Recent advances in radiology have enabled the early diagnosis of SCLC, and have prompted us to re-evaluate the effectiveness of surgery in SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…The updated search yielded six records. [5][6][7][8][9][10] A review of these results revealed no new evidence that would warrant substantive modification of the ASTRO Radiation Therapy for Small-Cell Lung Cancer guideline practice recommendations.…”
Section: Methods and Results Of The Asco Updated Literature Reviewmentioning
confidence: 99%
“…1 University of California, Davis, CA 2 American Society of Clinical Oncology, Alexandria, VA 3 Yale School of Medicine, New Haven, CT 4 Emory University School of Medicine, Atlanta, GA 5 Mayo Clinic, Rochester, MN 6 Weill Cornell Medicine, New York, NY 7 New Mexico Cancer Center, Albuquerque, NM 8 Dusty Joy Foundation, High Point, NC 9 University of Michigan School of Medicine, Ann Arbor, MI…”
Section: Affiliationsmentioning
confidence: 99%
“…The SCLC-associated invasive tumor growth and early metastatic dissemination are mainly driven by the mutational inactivation of RB1 and p53. Patients with limited stage (LS) or extensive stage (ES) SCLC are commonly given platinum-based chemotherapy, such as cisplatin and carboplatin, with the non-platinum agent etoposide as first-line treatment [74]. Immunotherapy using an anti-PD1 antibody, prolonged survival compared to standard chemotherapy against NSCLC; however, for SCLC the response rate to immunotherapy remains low, in the range of 15-30% [75].…”
Section: Small Cell Lung Cancermentioning
confidence: 99%